The Instructional Model for Using History of Science - (:unkn) unknown (EDAM, 2012)
This paper discusses the level of The Instructional Model for Using History of Science (UHOS) to explain the relationship between the history of science and science teaching. The UHOS model proposes four levels. Conceptual Level, Episternological Level, Sociocultural Level, and Interest Level. Each Level has sublevels with regards to types of historical knowledge, pedagogical approach and educational objectives. The UHOS model purports to help educator and researchers to explain their findings with an overarching theoretical framework.
Keywords: History of Science; Science Education; Instructional Model; ARGUMENTATION; CONCEPTIONS; PHILOSOPHY; KNOWLEDGE; EDUCATION; STUDENTS; EXPLICIT; BELIEFS